Comparative study of immediate functional loading and immediate non-functional loading of monocortical implants - Singh, J.P. (Med J Armed Forces India, 2015)
BACKGROUND: Attempts to shorten the overall length of treatment have focused on immediate loading, subsequent to implant placement. Prosthetic rehabilitation immediately after implant placement can be either functional or non-functional in nature. There is paucity of literature on the comparative evaluation of immediate functional and immediate non-functional loading of implants. This in-vivo study was undertaken to comparatively evaluate Immediate Functional Loading and Immediate Non-Functional Loading of monocortical implants with a follow-up period of 18 months. METHODS: 50 partially edentulous cases were selected for the study. The cases were divided into two groups. In first group (Group-1), 25 implants were subjected to immediate functional loading. In second group (Group-2), 25 implants were subjected to immediate non-functional loading. The crestal bone loss, clinical stability and degree of osseointegration of these two groups were comparatively evaluated. RESULTS: The crestal bone loss in both groups was within acceptable limits. The implant stability, which is a reflection of the status of bone-to-implant interface, was comparable in both the groups at different time intervals. Although, the ISQ values in Group-2 were slightly higher than those in Group-1, the results were not statistically significant. Radiodensity indicating degree of osseointegration at different time intervals in both groups was also comparable. CONCLUSION: Both the IFL and INFL protocols can be undertaken satisfactorily in rehabilitation using endosseous implants; however, the main factors for success in IFL and INFL are case selection, meticulous treatment planning and the precision of technique.